FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEAKTIFAN IBU HAMIL DALAM MENGIKUTI KELAS IBU HAMIL DI POLINDES TASIK SERAI WILAYAH KERJA PUSKESMAS SERAI WANGI - Een Husanah; Sherly Vermita; Riza Febrianti (Ensiklopedia Research and Community Service Review, 2026)
Active participation of pregnant women in maternal class programs plays a crucial role in improving knowledge, preparedness for childbirth, and overall maternal and neonatal health. However, participation rates remain varied and are influenced by multiple factors. This study aims to analyze the factors influencing the participation of pregnant women in maternal class programs at Polindes Tasik Serai, within the working area of Puskesmas Serai Wangi in 2025. This research utilized a correlational analytic design with a cross-sectional approach. The study sample consisted of 50 pregnant women selected through purposive sampling. Bivariate analysis was conducted using the Chi-Square test with a significance level of p 0.05. The results revealed a significant relationship between maternal knowledge and class participation (p = 0.000), with 88.9% of mothers with low knowledge being inactive in the class. Husband support also showed a significant relationship (p = 0.001), where 83.3% of mothers without husband support tended to be inactive. Furthermore, support from healthcare providers was significantly associated with participation (p = 0.000), with 88.5% of mothers who did not receive support from health workers being inactive in the class. In conclusion, maternal class participation is influenced by maternal knowledge, husband support, healthcare provider support, accessibility, and employment status. Therefore, improving education, increasing family involvement, and enhancing service accessibility should be prioritized to boost participation in maternal class programs.Keywords: Maternal Class Participation, Pregnant Women, Assoscated Factors